THE EFFECTS OF INTELLECTUAL AND EMOTIONAL INTELLIGENCE ON THE ACADEMIC ACHIEVEMENT OF MEDICAL STUDENTS - Yuditasari, Lelyana; Daeng Matadjo, Amelia Aziz; Firmansyah, Marindra (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2023)
Background:The selection of new students is crucial in the medical faculty. The selection may predict students' academic achievement during their learning journey. Different selection tools are commonly utilized, yet further investigation is required to ascertain the most effective instrument. While intellectual intelligence is frequently measured, emotional intelligence is scarcely employed in evaluating college applicants. This study seeks to examine how both intellectual and emotional intelligence levels influence a student's academic performance.Methods: This study employs a descriptive-analytical observational design with a cross-sectional perspective. Intellectual and emotional intelligence were assessed through an adapted questionnaire, The Stenberg Triarchic Abilities Test and the Emotional Intelligence Questionnaire. The questionnaire outcomes were validated against secondary data from student admissions, deploying the Intelligenz Structure Test and Edward Personality Preference Schedule for cross-validation. Furthermore, the Structural Equation Model - Partial Least Squares approach was utilized to analyze the questionnaire data.Results: The T-statistic value for intellectual intelligence is 3.134, with a path coefficient of 0.137. Meanwhile, the T-statistic value for emotional intelligence is 28.152, with a path coefficient of 0.83. Both intellectual and emotional intelligence influence students' academic achievement, with an R-Square value of 0.815, indicating that the exogenous variables (i.e., intellectual intelligence and emotional intelligence) can explain the endogenous variable of academic achievement up to 81.5%.Conclusion: Greater intellectual and emotional intelligence levels lead students to increase academic accomplishments.